2022
DOI: 10.1021/jacs.2c08505
|View full text |Cite
|
Sign up to set email alerts
|

Light-Reconfiguring Inhomogeneous Soft Helical Pitch with Fatigue Resistance and Reversibility

Abstract: Active engineering and modulation of optical spectra in a remote and fully reversible light is urgently desired in photonics, chemistry, and materials. However, the real-time regulation of multiple optical information such as wavelength, bandwidth, reflectance, and polarization is still a longstanding issue due to the lack of an appropriate photoresponsive candidate. Herein, we propose an additional “degree-of-freedom (DOF)” in a photo-modulated soft helix, and build up an unprecedented inhomogeneous helical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 67 publications
0
17
0
2
Order By: Relevance
“…Emission intensity of CPL at 743 nm as a function of the polarization angle in the polar coordinate system: (f) CPL intensity at 743 nm of the front and back sides of the cell, confirming high degrees of circular polarization at both sides of the LC cell; CPL intensity at 743 nm of (g) the front side and (h) the back side, indicating the same handedness of the CPL at both sides of the LC cell. Reproduced with permission from ref . Copyright 2022 ACS.…”
Section: Photo-responsive Lc Assembly To Modulate Cpl Signals and Rea...mentioning
confidence: 99%
See 1 more Smart Citation
“…Emission intensity of CPL at 743 nm as a function of the polarization angle in the polar coordinate system: (f) CPL intensity at 743 nm of the front and back sides of the cell, confirming high degrees of circular polarization at both sides of the LC cell; CPL intensity at 743 nm of (g) the front side and (h) the back side, indicating the same handedness of the CPL at both sides of the LC cell. Reproduced with permission from ref . Copyright 2022 ACS.…”
Section: Photo-responsive Lc Assembly To Modulate Cpl Signals and Rea...mentioning
confidence: 99%
“…As illustrated in Figure 10, we proposed an additional "degree of freedom" (DOF) in a photo-modulated soft helix by incorporating a unique absorbance photo-modulator, BTA-C5 (Figure 10a). 40 This allowed us to successfully establish an incomparable light-reconfigurable (from homogeneous to inhomogeneous helix) helical superstructure, thereby achieving dynamic, remote, light-driven control of both wavelength and bandwidth (Figure 10b). The phototunable helical superstructure with an inhomogeneous pitch exhibited a very broad bandwidth, especially for facilitating the realization of high g lum and broadband CPL (Figure 10b).…”
Section: Photo-responsive Lc Assembly To Modulate Cpl Signals and Rea...mentioning
confidence: 99%
“…While the quest for high-quality hard materials persists, there has been a surge in interest toward developing multifunctional soft materials. Soft materials may not possess the same level of strength and durability as hard materials, but their dynamic properties offer unique opportunities for the production of versatile advanced devices. Especially, smart soft materials have been designated as the cornerstone of the next generation of advanced devices and digital enhancement technologies. , Liquid crystals (LCs) with their controllable stimulus response and adaptive properties have been widely utilized in optoelectronic devices as one of the most promising soft materials. With the rapid advancement of chiral supramolecular chemistry in the past few decades, an increasing number of studies have focused on excellent circularly polarized luminescence (CPL)-active materials stemming from the regulation of a cholesteric LC (N*-LCs) medium through the rational design of chiral supramolecular self-assembly or co-assembly. , Normally, this kind of chiral self-assembled or co-assembled process can endow outstanding assembly function and give rise to the ordered and regular helical arrangement textures in N*-LCs, which is greatly beneficial to chiral amplification effect and chiral induction ability. More and more reports have demonstrated that N*-LCs can self-assemble as regular helical superstructure textures between chiral inducers and achiral dyes, which can effectively promote the chirality amplification effect of the achiral dyes through the chiral co-assembled process in the LC medium. Therefore, it is of great significance for the rational design of excellent supramolecular self-assembled and co-assembled CPL-active material.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Photochromic dithienylethene (DTE) derivatives, an ideal class of photoswitches, can undergo a reversible transformation between the open state and closed state triggered by light, along with changes in optical and electronic properties. [12][13][14][15][16][17][18][19] Their distinctive optical performances together with their excellent thermostability afford them a promising candidate in supramolecular systems, [20][21][22][23][24][25][26][27][28][29][30][31] liquid crystal superstructures, [32][33][34] and super-resolution imaging. [35][36][37] Introducing photoresponsive DTE units into chiral systems is a signicant and feasible strategy to construct dynamic chiral systems for mimicking and investigating life chirality.…”
Section: Introductionmentioning
confidence: 99%